2015
DOI: 10.1098/rspb.2015.2331
|View full text |Cite
|
Sign up to set email alerts
|

On being the right size: increased body size is associated with reduced telomere length under natural conditions

Abstract: Evolution of body size is likely to involve trade-offs between body size, growth rate and longevity. Within species, larger body size is associated with faster growth and ageing, and reduced longevity, but the cellular processes driving these relationships are poorly understood. One mechanism that might play a key role in determining optimal body size is the relationship between body size and telomere dynamics. However, we know little about how telomere length is affected when selection for larger size is impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
57
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 64 publications
8
57
0
Order By: Relevance
“…A possible explanation might lie with the fact that individuals with visible clinical signs of the disease were subjected to slower development in comparison to apparently healthy nestlings (field observation, Pineau K.). Indeed, previous studies have shown how telomeres might be shortened in individuals with faster development (Ringsby et al ., 2015). Thus, a lower metabolic rate attributable to slower growth might have masked any effects of infection on telomere erosion.…”
Section: Discussionmentioning
confidence: 98%
“…A possible explanation might lie with the fact that individuals with visible clinical signs of the disease were subjected to slower development in comparison to apparently healthy nestlings (field observation, Pineau K.). Indeed, previous studies have shown how telomeres might be shortened in individuals with faster development (Ringsby et al ., 2015). Thus, a lower metabolic rate attributable to slower growth might have masked any effects of infection on telomere erosion.…”
Section: Discussionmentioning
confidence: 98%
“…We predicted an interaction between brood size and relative nestling size in explaining the outcome variables, and the predicted interaction was indeed present for telomere length change and IL‐6. Thus, our results help reconcile previous experimental findings from jackdaws (Boonekamp et al., 2014) and starlings (Nettle et al., 2013) that the larger nestlings in large broods fare better than the smaller ones in terms of telomere attrition, with the negative associations between body size and telomere length observed in other field studies (Herborn et al., 2014; Noguera et al., 2015; Ringsby et al., 2015). These negative associations, in our data, are restricted to small broods, while positive associations appear in the largest broods.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, other things being equal, there should be a trade‐off between body size at the end of the fledgling period and telomere length (Reichert et al., 2014). In accordance with this possibility, several recent avian studies have observed associations between larger body size or faster growth and shorter telomere length at the end of development (Herborn et al., 2014; Noguera, Metcalfe, Boner, & Monaghan, 2015; Ringsby et al., 2015). In addition, Ringsby et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ongoing selection on body size and corresponding selection in the wild on telomere length have been demonstrated in a (correlative) quantitative genetics field study of sand lizards (using TRF) . Similarly, artificial selection for shortened tarsus length (a measure of body size) in house sparrows ( Passer domesticus ) resulted in a correlated shortening of telomeres (using qPCR) …”
Section: Telomeres As Biomarkers Of Aging and Correlates Of Fitness Cmentioning
confidence: 95%